(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article covers the theoretical and practical foundations of improving pedagogical mechanisms for preparing hearing-impaired children for inclusive education in the context of an educational cluster. During the study, the content of cooperation between the structural entities of the educational cluster, the continuity of pedagogical support, and the scientific foundations of forming an individual educational trajectory were analyzed. An analysis of existing practice showed that the use of only special pedagogical approaches in the process of preparing hearing-impaired children for inclusive education is not enough. Organizing this process on the basis of integrated cooperation between educational institutions, family, healthcare system, and higher education institutions increases efficiency. As a result of the research, an improved pedagogical mechanism was developed, consisting of the stages of diagnostics, pedagogical design, integrative cooperation, reflexive monitoring and individual development. This mechanism serves to develop the communicative, cognitive and social competencies of children with hearing impairment and their successful adaptation to an inclusive educational environment.